Body Mass Index and Body Satisfaction: Does Availability of Well-Fitting Clothes Matter?. (October 2021) - Grogan, Sarah; Gill, Simeon; Brownbridge, Kathryn; McChesney, Gillian; Wren, Paula; Cole, Jenny; Darby, John; Jones, Celina; Armitage, Christopher J.
Relatively little is known about the factors that mediate the relationship between high body mass index (BMI) and reduced body satisfaction. This is the first study to investigate whether availability of well-fitting clothes mediates this relationship. Eighty-five women with an age range of 18–81 years were 3D body scanned and weighed and measured at Time 1, and number of retailers stocking their sizes (determined through body scans) was calculated. At Time 2, they completed an online body satisfaction measure. Body satisfaction at Time 2 was predicted by both BMI and availability of well-fitting clothes in UK retailers at Time 1, with the two factors explaining 27% of the variance in body satisfaction. Availability of clothes size partially mediated the relationship between BMI and body satisfaction. Results suggest that the clothing retail sector might contribute to reducing body dissatisfaction by providing a wider range of choices for all sizes of consumer.